PENGARUH PENGGUNAAN DOMPET DIGITAL TERHADAP EFISIENSI PENCATATAN KEUANGAN PADA UMKM KULINER DI KABUPATEN GOWA - Dilla Safira; Muchriana Muchran; Nasrullah (STKIP Subang, 2026)
This study aims to analyze the effect of digital wallet usage on the efficiency of financial record-keeping among culinary MSMEs in Gowa Regency. The background of this research is based on the low level of systematic financial recording practices among MSMEs, alongside the increasing use of digital financial technology in business transactions. This study employs a quantitative approach using a survey method by distributing questionnaires to 100 culinary MSME actors in Gowa Regency. The data analysis technique used is Partial Least Square (PLS) with the assistance of SmartPLS software, through the evaluation of the outer model and inner model. The results show that all indicators have met the criteria of validity and reliability, with loading factor values above 0.70 and Average Variance Extracted (AVE) values above 0.50. Furthermore, the findings indicate that digital wallet usage has a positive and significant effect on the efficiency of financial record-keeping, with a path coefficient value of 0.847. The R-Square value of 0.717 indicates that the variable explains 71.7% of the variation in financial record-keeping efficiency.